Analysis of Translation Strategies on Movie Subtitle “Hotel Transylvania” - Miftah Komala Putri; Maya Kuswaty; Fadhli Dzil Ikrom; Ida Nuraida (Desanta Publisher, 2024)
This research is aimed to analyze the subtitles of movie “Hotel Transylvania” in non-equivalence words and analyze the method of translation strategies on its movie. The data source of research is subtitling text of the movie “Hotel Transylvania” in source language into target language, for the result subject that data analyzing on subtitle of the movie “Hotel Transylvania. The research methodology is descriptive qualitative: researcher collects data techniques by using some data collecting, and it is written on data transcriptions. The main result of this research, as follows: 1) in the data of non-equivalence words that there are some words identified as categorizes in the comments where the first categorization which the words are missed in the subtitling and it gotten in 0,32%, meanwhile, in the second categorization that there are words added in the subtitling with gotten 0,16%, and the third categorization is incorrect meaning where the meaning has inappropriate meaning and it gotten 0,51%.2)in data analyzing on movie subtitle “Hotel Transylvania” where the target language that classified into some of method and it can be described: word for word is gotten 7,60%, literal is gotten 37,01%, faithful is gotten 20,60%, semantic is gotten )0,18%, adaptation is gotten 0,80%, free is gotten 10,20%, idiomatic is gotten 10,60%, and communicative is gotten 10,01%. The conclusions of this research are some non-equivalence words that are identified on movie subtitling and data translation strategies are found in its subtitling, while the most common use of Newmark’s translation method is literal translation.